+0  
 
0
347
1
avatar

No idea how to solve this problem. 

 Sep 16, 2017
 #1
avatar+95884 
+1

We're not solving anything ....we just want to factor this as the difference of cubes

 

So we have

 

y^3 / 27    - x^9 / 216

 

Difference  of cubes  formula     

 

a^3 - b^3   =  (a - b)  (a^2  + ab  + b^2)

 

let a  = y / 3      b  = x^3 / 6       a^2  = y^2 / 9      ab  =  [y x^3 ] / 18      and    b^2 =  x^6 / 36

 

So we have 

 

( y / 3 - x^3 / 6) (  y^2 / 9  +   [y x^3 ] / 18  + x^6/ 36  )

 

 

cool cool cool

 Sep 16, 2017

12 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.